Menyingkap Ekspresi Ketuhanan dalam Puisi: Telaah Kognitif Pragmatik atas Bahasa Spiritual - Abu Katili, Adriansyah; Mahmud, Muzdalifah (Jurnal Bahasa, Sastra, dan Budaya, 2025)
This article explores the expression of divinity in poetry. The poems analyzed are"Siang Arafah" by Suminto A. Sayuti and "God's World" by Edna St. Millay. Thisresearch was conducted using a cognitive pragmatic approach, incorporatingAustin's speech act theory and Sperber and Wilson's theory of relevance. Theresearch method employed the principles of discourse analysis, namely theprinciples of local interpretation and analogy. This study found that Sayuti's poemsutilize expressive speech acts. Using relevance theory, it was found that the poetsfrequently use diction that clarifies the meaning of the expressive speech acts to thereader. Meanwhile, Millay's poem "God's World" contains expressive speech acts.Millay also uses diction to enable the reader to interpret the meaning of theutterances. The meaning of both poems is a longing for God.